Comparison of Macular Thickness in Diabetic Macular Edema Using Spectral-Domain Optical Coherence Tomography and Time-Domain Optical Coherence Tomography - Masashi Kakinoki; Taichirou Miyake; Osamu Sawada; Tomoko Sawada; Hajime Kawamura; Masahito Ohji (Journal of Ophthalmology)
Purpose. To compare the macular thicknesses in diabetic macular edema (DME) measured with spectral-domain optical coherence tomography (SD-OCT) and time-domain (TD) OCT. Patients and Methods. The average macular thicknesses of 50 eyes of 29 patients with DME were measured using SD-OCT and TD-OCT. Results. The mean macular thicknesses measured with TD-OCT and SD-OCT were 401.5±117.8 μm (mean ± SD) and 446.2±123.5 μm, respectively. The macular thicknesses measured with the two devices were well correlated (Pearson's product moment correlation, r=0.977, P<0.001). A significant correlation was found between the best-corrected visual acuity and the retinal thickness measured by TD-OCT and SD-OCT (Pearson's product moment correlation, TD-OCT, r=0.34; P<0.05; SD-OCT, r=0.32; P<0.05). Discussion. The mean macular thickness measured with SD-OCT was about 45 μm thicker than that measured with TD-OCT. Attention should be paid when comparing data obtained using different OCT machines.